Курган ранньоскіфського часу біля с. Шутнівці у середньому Подністров'ї - Гуцал, А.Ф.; Гуцал, В.А.; Могилов, О.Д. (Археологія, 2022)
Стаття присвячена публікації матеріалів кургану 5 могильника біля с. Шутнівці Хмельницької обл.
Поховання, досліджене 1999 р., було здійснене в
дерев’яній стовповій гробниці та належить до
ранньоскіфського часу. The article is dedicated to the description of the mound no. 5 contents near Shutnivtsi village of Kamianets-Podilskyi region,
Khmelnytskyi Oblast. The monument was explored in 1999 by the Expedition of Kamianets-Podilskyi University and headed
by A. F. Hutsal.
The height of the mound was 0.5—0.6 m, the diameter — 8 m. The embankment consisted of soil with stones. Under the
embankment, after rabotage, there were discovered the remains of stone structures concentrated above and around the grave. In
section, they had a shape close to the square with dimensions of 5.5 × 4.5 m. Its outer contours were limited by large stones. They
lay in three parallel rows close to each other. Between them and on top of them there were small stones. Under the mound there
was found a burial vault with four pillars. It was located along the northwest-southeast axis. Its dimensions were 2.3 × 3.35 m,
the depth was 0.95—1.0 m. The north-western wall of the burial chamber was obviously lined with stones. The floor of the crypt
was paved with stone tiles. They were closely adjacent to each other, but in the southern part of the grave and in the western
corner the tiles were taken away by robbers. There were pillar pits in each corner of the grave. They were round in section. Their
bottom was paved with stone tiles. Depth: 0.97—1.15 m; diameter: 0.71—0.75 m.
All the pits were filled with stones and grey earth, and below them there was clay, sand, and pebbles. Only wooden decay remained
from the pillars. The thickness of the pillars was 0.2—0.3 m. They could have supported the wooden structure of the ceiling of the crypt.
The burial chamber was heavily robbed. Almost all inventory was removed or stolen by them. Only some areas survived. In the
northern corner of the crypt, on a stone floor tile, a part of the lower human jaw, four bronze pins and a piece of ocher were found. The
clay ladle and fragments of the pot were found near the south-western wall. The bronze arrowhead was discovered in the eastern corner.
Most of the objects were moved from their original place. Parts of the bones of the human skeleton were found in the
burial pit. Fragments of several ladles, two pots and a bowl were examined in different places. About 265 glass beads and their
fragments were also discovered in the grave.
The mound can be dated to the early Kelermes period (middle — second half of the 7th century BC). It could have belonged
to a wealthy family of one of the local communities. It can also be assumed that the people buried in the mound might have been
the clergy of a religious body.